The Financial Anxiety of Icelandic University Students; Relation to socioeconomic status and consequences - María Lena Sigurðardóttir 1990- (2023)
This study aims to explore financial anxieties among university students regarding their socioeconomic status (SES) and its consequences. It addresses four key questions: 1) Do Icelandic undergraduates suffer from financial anxiety? 1a) Do students from low SES suffer more from financial anxiety than others? 1b) What is the relationship between financial worries and student’s general financial and family environment? 2) Does a student’s financial situation relate to their educational progression? The Financial anxiety scale (FAS) was utilized and a questionnaire about financial and family circumstances constructed. Undergraduate students at the University of Iceland bachelor's students were contacted for the study and 412 responded. Findings reveal that Icelandic students experience financial anxiety, but no relations between SES of students and parents were detected. Age and gender affected the scores of the students on the scale. Notably, students don't directly link their or their parents' SES to current financial anxiety. However, more specific parental situations such as their willingness to aid students and students’ feelings toward asking them for aid demonstrate a connection was related to financial anxiety. Financial anxiety negatively influences self-assessed educational attainment and achievement to a large degree. The study emphasizes the need for further investigation into factors driving financial anxiety in the diverse student population and its implications for dropout and progression. Overall, the findings highlight the necessity to address financial anxiety's complex dynamics within the university student population. Rannsókn þessi var gerð með það að markmiði að kanna fjárhagsáhyggjur hjá háskólanemum í tengslum við félags- og fjárhagsstöðu þeirra sem og afleiðingar. Stefnt var að, að svara fjórum spurningum: 1) Þjást háskólanemar af fjárhagskvíða, 1a) Þjást nemar sem búa við verri félags- og fjárhagsstöðu frekar en aðrir af fjárhagskvíða, 1b) Hvert er sambandið á milli fjárhagsáhyggja og ...